Approaching the Internet of things (IoT): a modelling, analysis and abstraction framework. (3rd October 2013) - Ikram, Ahsan; Anjum, Ashiq; Hill, Richard; Antonopoulos, Nick; Liu, Lu; Sotiriadis, Stelios; Mustafee, Navonil; Bessis, Nik; Barolli, Leonard; Chen, Xiaofeng; Xhafa, Fatos
Summary The evolution of communication protocols, sensory hardware, mobile and pervasive devices, alongside social and cyber‐physical networks, has made the Internet of things (IoT) an interesting concept with inherent complexities as it is realised. Such complexities range from addressing mechanisms to information management and from communication protocols to presentation and interaction within the IoT. Although existing Internet and communication models can be extended to provide the basis for realising IoT, they may not be sufficiently capable to handle the new paradigms that IoT introduces, such as social communities, smart spaces, privacy and personalisation of devices and information, modelling and reasoning. With interaction models in IoT moving from the orthodox service consumption model, towards an interactive conversational model, nature‐inspired computational models appear to be candidate representations. Specifically, this research contests that the reactive and interactive nature of IoT makes chemical reaction‐inspired approaches particularly well suited to such requirements. This paper presents a chemical reaction‐inspired computational model using the concepts of graphs and reflection, which attempts to address the complexities associated with the visualisation, modelling, interaction, analysis and abstraction of information in the IoT. Copyright © 2013 John Wiley & Sons, Ltd.